A policymaker’s guide to understanding youth livelihood aspirations in Myanmar - de Silva, Sanjiv; Senaratna Sellamuttu, Sonali; Arulingam, Indika; Joshi, Deepa; Moet, Palal (WorldFish, 2022)
The International Water Management Institute (IWMI) and WorldFish conducted a study with young people from a fishing community in the Ayeyarwady Delta of Myanmar. The study sought to understand the livelihood aspirations of these young people and how they were connected to eventual livelihood realities.